Investigation of plasmodium vivax rhomboid-like protease 1 compared to plasmodium falciparum rhomboid protease 1 in erythrocytic cycle - Touchchapol Mataradchakul (2019)
© 2018, Chiang Mai University. All rights reserved. Plasmodium Rhomboids (ROM) are members of a family of serine proteases that play key roles in erythrocyte invasion. To date, the P. vivax ROM-like 1 (PvROM-like 1) protein has not been characterized. This study aimed to detect the rhomboid proteins in the erythrocytic cycle of the malaria parasite. Infected blood samples were collected from malaria clinics in Mae Sot, Tak, Thailand during September 2013-May 2014. Extracted RNA was examined for the presence of Pvrom-like 1 by RT-PCR. The corresponding protein was characterized using SDS-PAGE, Western blot and immunofluorescence assays. The apparent molecular weight of PvROM-like 1 protein was estimated to be approximately 30 kDa using polyacrylamide gel electrophoresis and Western blotting. PvROM-like 1 and PfROM1 proteins could be detected by use of anti-PfROM1 and anti-PbROM1 antibodies, but not with an anti-DroROM1 antibody. Our results show that PvROM-like 1 protein is found in all erythrocytic stages of the P. vivax cycle and may function in the invasion of malaria into red blood cells.